ANALISIS KEGIATAN MEWARNAI UNTUK MENGEMBANGKAN ASPEK SENI PADA ANAK DI KELOMPOK BERMAIN - Maharani, Melani Firdha; Fahmi, Fahmi; Wulandari, Retno (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
Art can be used in developing creative potential. This potential can be seen from the way of thinking critically and the ability to think, very high curiosity, able to express oneself in public, able to express original ideas and opinions, dare to be different and dare to take risks, able to accept other people's opinions, also respect yourself and others. The purpose of this article is so that children can develop aspects of artistic development that exist in children and children are free to be creative according to children's imagination through these coloring activities. As well as setting up a learning environment that can improve aspects of artistic development in children. Methodology This study uses literature review, literature review here is an analytical activity that can be in the form of criticism of a research that is being carried out on a particular topic which is part of a scientific field. The result is that in order to manage and develop aspects of artistic development in children through coloring activities so that they can help children to improve early childhood art, of course teachers must know the stages of art development in early childhood, especially in play group units (kb).